1999
DOI: 10.1034/j.1399-3003.1999.14b23.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of MCP‐1 levels in BALF and serum in patients with interstitial lung diseases

Abstract: It has previously been reported that the expression of monocyte chemoattractant protein-1 (MCP-1) in the lung tissues of patients with idiopathic pulmonary fibrosis (IPF) was different from that in the tissues of patients with other interstitial lung diseases (ILDs). The aim of this study was to determine whether this difference reflects the amount of MCP-1 in the bronchoalveolar lavage fluid (BALF) or serum of patients with ILD, and whether such a correlation, if it exists, is clinically useful. MCP-1 concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(80 citation statements)
references
References 24 publications
3
73
2
2
Order By: Relevance
“…CCL2 and CCL3 are significantly upregulated both in BAL fluid of patients with IPF and in bleomycin-induced lung fibrosis [11, 12]. In this study, we observed a difference in CCL2 levels in BAL fluid between the surviving and nonsurviving patients with IPF whereas CCL3 levels in BAL fluid did not differ.…”
Section: Discussioncontrasting
confidence: 34%
See 1 more Smart Citation
“…CCL2 and CCL3 are significantly upregulated both in BAL fluid of patients with IPF and in bleomycin-induced lung fibrosis [11, 12]. In this study, we observed a difference in CCL2 levels in BAL fluid between the surviving and nonsurviving patients with IPF whereas CCL3 levels in BAL fluid did not differ.…”
Section: Discussioncontrasting
confidence: 34%
“…Several studies have demonstrated the presence of CC chemokines in human interstitial lung diseases [10,11,12,13,14,15]. Augmented production of macrophage chemoattractant protein-1 (CCL2) by metaplastic epithelial cells and its increase in parallel with disease activity were reported in IPF [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its well known chemoattractant activity for mononuclear leukocytes [30][31][32][33][34][35], MCP-1 has direct pro-fibrogenic activity as demonstrated by its capacity to stimulate fibroblast collagen expression via endogenous upregulation of TGF b production [36]. In addition, analyses of lung tissue and bronchoalveolar lavage (BAL) fluid from patients with idiopathic pulmonary fibrosis (IPF) as well as in animal models have demonstrated elevated levels of MCP-1 expression [37][38][39][40][41][42]. The precise in vivo role of MCP-1 and its cognate receptor CCR2 remains uncertain, but its importance in pulmonary fibrosis has been documented and appears to be unrelated to its pro-inflammatory activity [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…These mediators belong to the CXC family (α subfamily) that selectively attracts neutrophils. The MCP-1 levels in bronchoalveolar lavage fluid and sera in patients with idiopathic pulmonary fibrosis and other types of IP are increased [40,41,42]; likewise, increased levels of CXC chemokines are associated with pathological conditions in IP [43,44,45]. The blood levels of some inflammatory chemokines, e.g.…”
Section: Discussionmentioning
confidence: 99%